Improving reactivity of naphthalimide-based GST probe by imparting TPP cation: Development and application for live cell imaging. (15th January 2023) - Fujikawa, Yuuta; Terakado, Kenta; Nezu, Sayaka; Noritsugu, Kota; Maemoto, Yuki; Ito, Akihiro; Inoue, Hideshi
Graphical abstract: Abstract: Glutathione S-transferases (GSTs) are a superfamily of multifunctional enzymes comprising multiple classes and subtypes. This paper describes the synthesis and characterization of TPPBN-1, a naphthalimide derivative conjugated with a triphenylphosphonium (TPP) cation. When 4-bromonaphthalimide (BrNaph), a previously characterized GST substrate, was conjugated to a TPP cation, the conjugate showed increased reactivity towards most alpha- and mu-class GSTs, particularly the GSTA2 subtype, compared to the parent compound, but hardly towards Pi-class GSTs. Using this probe with enhanced reactivity, the enzymatic activity of endogenous GSTA1/2 in HepG2 cells was visualized by confocal fluorescence microscopy. The results demonstrated that modification with TPP cations, which are often used as tags for targeting mitochondria, can be used to enhance the reactivity of probes for specific GST subtypes.